Life Goals Over Time Among Homeless Adults in Permanent Supportive Housing. Issue 3 (14th March 2018) - Wenzel, S.L.; Rhoades, H.; Moore, H.; Lahey, J.; Henwood, B.; La Motte‐Kerr, W.; Bird, M.
Abstract: Permanent supportive housing (PSH) is a widely‐accepted solution to the challenge of chronic homelessness. While housing support and retention, physical health, and healthcare continue to be important for formerly homeless persons in PSH, "higher‐order" and humanistic needs such as thriving have received less attention and as a result are less well understood in this population. One important indicator of thriving is the ability to establish and articulate life goals. This study utilizes longitudinal data from 421 formerly homeless adults prior to their move into PSH, and at 3‐, 6‐ and 12‐months after move‐in (369 respondents completed all four interviews), to examine what life goals are articulated by this population and how those goals change over time. Prior to housing, most respondents articulated housing attainment as their primary life goal, whereas at follow‐up interviews health goals, housing relocation, and financial goals became more prevalent. Aspirational goals (e.g., independence, self‐improvement, artistic pursuits) were also common, but demonstrated a decrease over time in housing. Relationship goals remained common and consistent over time. Findings indicate that housing is a necessary, but perhaps not sufficient, step for improving thriving among formerly homeless adults. Implications for practice and future research are discussed. Highlights: Health, financial, and housing relocation goals increased over time in housing. Aspirational goals (e.g., independence, self‐improvement, artistic pursuits) decreased over time. Social relationship goals remained stable over the first year in PSH. Most respondents identified housing as a platform enabling them to meet or strive for life goals. Housing is a necessary but perhaps not sufficient step for improving thriving among those in PSH.